2019
DOI: 10.1111/jan.13914
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between workplace characteristics and work ability in residential aged care: What is the role of work–life interaction?

Abstract: Aims To examine whether the work–life interface (through work–family conflict and overall work–life balance) moderates the relationship between work ability and workplace demands and resources. Design This study used a cross‐sectional survey design to collect data from 426 employees working in residential aged care. Methods A paper‐based questionnaire was distributed to all permanent and casual employees at eight aged care facilities in Melbourne, Australia, between June ‐ September 2013. Moderation analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…For example, WFC has been found to both mediate and moderate the relationship between musculoskeletal pain and work-place characteristics. 35,36 Weale et al 37 reported that WFC moderated the relationship between workplace characteristics and work ability (the ability to work at one's best 38 ). Weale et al 39 found that WFC mediated the relationship between workplace characteristics (relationships with management, poor relationships with colleagues, and safety climate) and job satisfaction; however, these studies did not include people WFH, so it is unknown whether these findings apply in a WFH context, irrespective of whether WFH is undertaken on a recommended/mandatory basis or by negotiation.…”
Section: Work-family Conflict and Fwc As Potential Mediators In The R...mentioning
confidence: 99%
“…For example, WFC has been found to both mediate and moderate the relationship between musculoskeletal pain and work-place characteristics. 35,36 Weale et al 37 reported that WFC moderated the relationship between workplace characteristics and work ability (the ability to work at one's best 38 ). Weale et al 39 found that WFC mediated the relationship between workplace characteristics (relationships with management, poor relationships with colleagues, and safety climate) and job satisfaction; however, these studies did not include people WFH, so it is unknown whether these findings apply in a WFH context, irrespective of whether WFH is undertaken on a recommended/mandatory basis or by negotiation.…”
Section: Work-family Conflict and Fwc As Potential Mediators In The R...mentioning
confidence: 99%
“…Risk management strategies for MSD are still largely focused on management of physical hazards 38,39 and a shift to multifaceted interventions, taking into account all possible contributing factors, including psychosocial hazards and those arising from the work–life interface, is required to adequately manage MSDs 40,41 . Examining the relationship between health outcomes, WFC, and work‐related hazards may identify intervention points to improve health outcomes for individuals, potentially extending working life 42 …”
Section: Introductionmentioning
confidence: 99%
“…Many working conditions can change due to a voluntary employer change, which may have a direct impact on work ability-and of course job satisfaction-such as leadership quality, work-privacy conflict, travel time to work, colleagues, work tasks, influence at work, working environment and work equipment (Grund 2009;Carless and Arnup 2011;Garthe and Hasselhorn 2020). Several studies confirmed the relationship between physical and psychological working conditions and work ability (Alavinia 2008;van den Berg et al 2008;Sanders et al 2011;Attarchi et al 2014;Weale et al 2019). It can also be assumed that only those employees change, who expect an improvement, which implies that changers to some degree may constitute a selective group.…”
Section: The Honeymoon-hangover Effect For Work Abilitymentioning
confidence: 98%